Measuring Master Students’ Online Learning Perceptions and Satisfaction during Covid-19 Crisis in Morocco - JAMIAI, Abdelmajid (International Journal of Language and Literary Studies, 2021)
The implementation of technology in higher education is highly considered in research conducting during Covid-19 crisis in Morocco. This article examines students’ perceptions and the degree of satisfaction in online classes for one semester during the emergency of Covid-19 pandemic. The research design for this study is quantitative in which a questionnaire was used to collect data from thirty-two (32) respondents who are enrolled in two Master Programs of ‘Applied Language Studies and Research in Higher Education’ and ‘Language, Communication, and Society’ at the Faculty of Letters and Human Sciences of Dhar Mehraz of Sidi Mohamed Ben Abdellah University in Morocco as a convenient sampling. The SPSS (Statistical Package for Social Sciences) was used to analyze the retrieved data via e-mails. The findings of this study demonstrate that the majority of Master students would like to resort to hybrid education instead of online classes per se. They also show that online learning satisfaction does not receive high levels of agreement among the respondents. The paper ends up with some recommendations for the implementation of online education in higher education.